How persuasive is phishing email? The role of authentic design, influence and current events in email judgements. Issue 2 (1st February 2019) - Williams, Emma J.; Polage, Danielle
ABSTRACT: Fraudulent emails, otherwise known as phishing emails, use a range of influence techniques to persuade individuals to respond, such as promising a monetary reward or invoking a sense of urgency. The current study explored a number of factors that may impact the persuasiveness and trustworthiness of emails by examining participant judgements of 20 pre-designed emails that varied according to (a) whether they used loss or reward-based influence techniques, (b) whether they contained particular authentic design cues, (c) whether they referenced a salient current event (the Rio Olympics), and (d) whether participants had been previously exposed to information regarding online scams in general. Results suggest that the presence of authentic design cues and the type of influence technique used significantly impacted participant judgements. Findings are discussed in relation to theoretical models of phishing susceptibility.